Impact of preinterventional tricuspid regurgitation on outcome of MitraClip therapy in patients with severely reduced ejection fraction. Issue 1 (15th March 2020) - Gyoten, Takayuki; Messroghli, Daniel; Schenk, Soeren; Rochor, Kristin; Grimmig, Oliver; Just, Soeren; Fritzsche, Dirk
Abstract : Aim: To evaluate the impact of preinterventional moderate-to-severe functional tricuspid regurgitation (FTR) on early outcome after percutaneous edge-to-edge mitral valve repair (pMVR) with MitraClip procedures for functional mitral regurgitation (FMR) in patients with heart failure with reduced ejection fraction (HFrEF). Methods and results: From January 2013 to December 2017, 80 patients with HFrEF (ejection fraction 22%±5.3%) and FMR (grade 3.0±0.36) underwent successful pMVR. The 3-year actuarial survival was 58%. However, 73% (n=22) of non-survivors died of cardiac failure within 1 year. Patients were categorised into none-to-mild (n=36) and moderate-to-severe (n=44) postinterventional FTR groups according to pre-MitraClip tricuspid regurgitation grade. Cox regression analysis on 1-year survival demonstrated an impact of FTR severity (HR=1.8, 95% CI 1.01% to 3.09%, p=0.047), preoperative New York Heart Association class (HR=2.8, 95% CI 1.2% to 6.5%, p=0.015) and peripheral artery disease (HR=5.4, 95% CI 1.6 to 18, p=0.0054). Kaplan-Meier analysis showed that 1-year cardiac death was higher in the moderate-to-severe FTR group (p=0.048). In our study, 77% of pre-MitraClip moderate-to-severe FTR cannot be significantly reduced. Post-MitraClip moderate-to-severe FTR grade was related to lower survival (p<0.001). Conclusion: In patients with HFrEF treated with MitraClip for FMR, moderate-to-severe FTR was an independent predictor of cardiac death within 1 year. To improve survival, additional therapy to residual FTR should be considered in early phase after MitraClip therapy.